Challenging the Constraints of Neoliberalism and Biomedicalism: Repositioning Social Work in Mental Health. (April 2022) - Brown, Catrina; Johnstone, Marjorie; Ross, Nancy; Doll, Kaitrin
This article explores the impact of neoliberalism and biomedicalism on social work mental health care practice through presenting the results of a Canadian provincial study which illustrates the experiences of social work service users, providers, and supervisors. While Canada has a universal health care program, the intensification of the free-market approach is evident in the shifts from public sector support to growing rationalization and marked cutbacks to the provision of social welfare services. The specific impact of neoliberal economic restraint on social justice in mental health services has pressured practitioners to adopt medicalized, short-term strategies, under efficiency-based models. The participants in this study reported significant co-occurring concerns with the state of mental health service delivery, and results suggest social work is increasingly co-opted by the conservative individualizing, pathologizing, and contextualizing dominant biomedical framework in the provision of mental health social services and lack of professional practice autonomy.